Increased intermediate CD14++CD16++ monocyte subset levels associate with restenosis after peripheral percutaneous transluminal angioplasty. (October 2016) - Wildgruber, Moritz; Czubba, Maria; Aschenbrenner, Teresa; Wendorff, Heiko; Hapfelmeier, Alexander; Glinzer, Almut; Schiemann, Matthias; Zimmermann, Alexander; Eckstein, Hans-Henning; Berger, Hermann; Wohlgemuth, Walter A.; Meier, Reinhard; et al.
Abstract: Background and aims: We aimed at studying the association of three major human monocyte subsets after percutaneous transluminal angioplasty (PTA) in patients with femoropopliteal disease. Methods: We prospectively studied 67 sequential patients (40 male, 27 female; mean age 71 ± 11 years) treated with femoropopliteal angioplasty. Multi-color flow cytometry characterized monocyte subsets from venous blood for expression of CD14 and CD16 and intracellular myeloperoxidase (MPO) prior to, and 3, 6 and 12 months post PTA. Analyses tested associations between monocyte subsets and risk for restenosis. Results: 16/67 patients (24%) developed restenosis within 12 months after PTA. Patients with hyperlipidemia had increased risk for restenosis (HR = 1.7, 95% CI 0.7–2.9, p  = 0.001). Increased baseline monocytes associated with an increased risk of late restenosis (HR = 4.9, 95% CI: 1.3–18.6, p  = 0.047). CD14 ++ CD16 ++ 'intermediate' monocytes assessed at baseline, and after 3, 6, and 12 months significantly associated with the risk for subsequent restenosis: HR = 3.9 (95% CI: 2.4–6.5, p  = 0.029), HR = 5.7 (95% CI = 0.7–44.7, p  = 0.013), HR = 6.5 (95% CI: 2.5–16.9, p  = 0.001) and HR = 1.5 (95% CI = 1.4–15.5 p  = 0.001), respectively. Moreover, the probability for freedom of restenosis decreased with increased levels of intermediate subsets at 12 months after PTA. Additionally, intracellular MPO expression in CD14 ++ CD16 ++ measured at 3, 6 and 12 months associated with an increased restenosis risk (HR = 1.5, 95% CI: 0.8–2.1, p  = 0.214, HR = 1.9, 95% CI: 1.0–2.3 p  = 0.051 and HR = 1.4, 95% CI: 1.0–1.8, p  = 0.052). Conclusions: Our results imply altered innate immunity after angioplasty. Elevated CD14 ++ CD16 ++ intermediate monocyte frequencies and increased MPO expression may identify individuals at heightened risk for restenosis. Highlights: Monocyte subset distributions are differentially affected by angioplasty of lower limb arteries in patients with and without restenosis. Increased frequencies of CD14 ++ CD16 ++ 'intermediate' monocytes are predictive for the development of restenosis after percutaneous transluminal angioplasty of lower limb arteries. 'Intermediate' monocytes display an upregulated intracellular myeloperoxidase content, associated with a higher restenosis risk. Monocyte subset distributions and phenotype may indicate individuals at higher risk for restenosis.